NLC Delivery of EGFP Plasmid to TM4 Cell Nuclei for Targeted Gene Therapy - Nurul Jummah; Satrialdi Satrialdi; Aluicia Anita Artarini; Anindyajati Anindyajati; Diky Mudhakir (Advanced Pharmaceutical Bulletin, 2024)
Purpose: This study evaluated whether a nanostructured lipid carrier (NLC) delivery system could safely and accurately deliver nucleic acids to the cell nucleus using the enhanced green fluorescent protein (EGFP)-C1 plasmid model. Methods: The NLC was formulated using the emulsification method and equipped for cationic lipid-mediated transfection with 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP), which interacts electrostatically with nucleic acid. The NLC attributes, including size, polydispersity index, and zeta potential, were assessed by dynamic light scattering (DLS). The morphological structure was analyzed using transmission electron microscopy. Entrapment efficiency was evaluated by a direct method. Cellular uptake mechanisms of pEGFP-C1-NLC and the ability of pEGFP-C1 to penetrate the nucleus of TM4 cells to express EGFP were observed using confocal microscopy. Results: pEGFP-C1-NLC exhibited particle sizes in the range 56-88 nm with a particle charge range of -6.0 to+1.3 mV. The polydispersity index<0.5 showed good size uniformity, and entrapment efficiency of pEGFP-C1in the NLC was 92.06±2.295%. The NLC formulation was internalized predominantly via caveolae-mediated endocytosis, as indicated by EGFP expression following successful delivery of pEGFP by the NLC into the cells. Conclusion: NLC formulation could deliver genetic material to the nucleus and could be considered a gene therapy candidate for spermatogenesis.